Analysis of Project Time and Cost using the Crash Program Approach - Dewanto, Wido Prasetya; Yustisia, Henny (Universitas Negeri Padang, 2024)
Project acceleration is a solution to speed up project completion. Project acceleration has various alternatives, including adding overtime hours and adding labor. This research aims to assess the changes in project time and costs following acceleration efforts through options such as increasing working hours (overtime) and adding labor. The project acceleration method used is the crash program method, supported by the Microsoft Project application. The research results show that for the option of adding overtime hours, with 1 hour of overtime, the cost was Rp 27,011,372,606.28 and the duration was 204.13 days; for 2 hours of overtime, the cost increased to Rp 27,156,499,375.32 with a duration of 199.01 days; with 3 hours of overtime, the cost was Rp 27,307,828,821.71 and the duration shortened to 194.62 days; and with 4 hours of overtime, the cost was Rp 27,465,750,984.13 with a duration of 190.92 days. For the alternative of adding labor, under a scenario equivalent to 1 hour of overtime, the cost was Rp 26,846,481,892.32 and the duration was 204.13 days; with 2 hours of overtime, the cost was Rp 26,797,919,204.37 with a duration of 199.01 days; with 3 hours of overtime, the cost decreased to Rp 26,746,499,142.20 and the duration was 194.62 days; and for 4 hours of overtime, the cost was Rp 26,703,236,580.04 with a duration of 190.92 days. Thus, adding labor is identified as an effective alternative due to its economical cost, even though it results in the same project acceleration duration.